Exploring the impact of AI competencies, B2B marketing capabilities and disruptive innovation on marketing performance: The mediating role of growth hacking - Utama, Adi; Johan, Ahmad; Hidayat, Yosep Rahman (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
Purpose – This study explores the relationships between AI competencies, B2B marketing capabilities, disruptive innovation, on marketing performance. It also investigates the mediating role of growth hacking in these relationships.Design/methodology/approach – A quantitative approach was employed, with an online questionnaire distributed via Google Forms to 350 managers/supervisors from B2B companies in Jakarta and Bandung. The data analysis technique used is partial least squares structural equation modeling (PLS-SEM), processed using Smart PLS 3.0 software, to assess the direct and indirect relationships between the variables.Findings – The study found that AI competencies and disruptive innovation significantly enhance growth hacking, which positively influence marketing performance. Growth hacking was identified as a significant mediator in the relationship between B2B marketing capabilities and marketing performance, highlighting its role in amplifying the impact of marketing strategies.Research limitations/implications – The study's sample size is limited to a specific region, and the cross-sectional design restricts the ability to establish causality (only companies from Jakarta and Bandung City). Future research could expand the sample and explore longitudinal effects to strengthen the generalizability of the findings.Practical implications – For practitioners, the findings emphasize the importance of integrating AI and disruptive innovation to enhance marketing capabilities. Leveraging growth hacking techniques can maximize marketing performance in B2B environments.Originality/value – This study contributes to the literature by linking AI competencies, disruptive innovation, and growth hacking to marketing performance within B2B contexts, providing valuable insights into how these elements interact to drive organizational success.